Pakistan Panel Survey, 1986-1991 - International Food Policy Research Institute (International Food Policy Research Institute, 2000)
The questionnaire was administered in 14 rounds over five years to approximately 800 rural households. Topics include household characteristics and composition; anthropometry, child health and nutrition; land ownership and tenure; agricultural production and disposition by season; household expenditures on labor, factors of production, food and other nonfood elements; male and female labor use; time allocation of household members(male and female); household asset ownership; long and short term credits; livestock and poultry ownership and income; male and female nonfarm activities and income; women's fertility history; pensions, other transfer incomes, income from trade and crafts. Community/village level information were collected on crop yields, crop prices and irrigation water rate, the daily wage rate on farm and nonfarm activities, the price of essential food and nonfood items, the availability of public services in a village, rural education, migration and employment. Data were also collected on technology adoption and technical skills of wheat farmers, labor on different farm activities and returns to labor.